2020
DOI: 10.1109/access.2019.2963423
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Cable Rejuvenation by Simulating Cable Operation

Abstract: Further research on retired cable rejuvenation via heat treatment was investigated in this paper. Three retired cables with service year of 7, 15 and 30 years were used and annealed at different temperatures following two different heat treatment methods. In the first test, two short cables with a length of 5 m were prepared and cut into five equal segments. Four segments of each cable were annealed at 90, 95, 100, and 105 • C to simulate the cable operation. Then, the cross-linked polyethylene (XLPE) from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Relevant parameters are listed in Table 4. From Figure 7 (a), a small shoulder peak located at 50 to 90 • C exists in most of the specimens expect for S4, which indicates the thermal history, causing by the degassing process during manufacture or overheating process during the actual operation of the cable [2]. For S4 to S1, it can be found that the melting range is widened with the increase of the operating period.…”
Section: ) Results Of Dsc Measurementmentioning
confidence: 94%
“…Relevant parameters are listed in Table 4. From Figure 7 (a), a small shoulder peak located at 50 to 90 • C exists in most of the specimens expect for S4, which indicates the thermal history, causing by the degassing process during manufacture or overheating process during the actual operation of the cable [2]. For S4 to S1, it can be found that the melting range is widened with the increase of the operating period.…”
Section: ) Results Of Dsc Measurementmentioning
confidence: 94%
“…However, it is hard to obtain the parameters of c eq1 , tan δ 1 , c eq2 and tan δ 2 respectively. Therefore, Equation ( 16) is approximated to obtain Equation (17).…”
Section: Equivalent Transient Thermal Circuit Delaminated Model Of Xl...mentioning
confidence: 99%
“…However, due to its high cost of labour and material resource, long-term operation and high consumption of sample, few relevant investigations have been conducted, especially for high voltage power cable. Y. Xie et al [16,17] conducted different simulating cable operation test to the retired XLPE power cables. It is found that the thermal and electrical properties of each layer of the cable insulation are improved in varying degrees under the short-term high temperature heat treatment, due to the annealing effect.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to its high cost of labor and material resources, long-term operation, and high consumption of sample, there are few relevant investigations, especially in the high voltage power cable. Y. Xie et al [11,12] conducted different simulation cable operation tests on retired XLPE power cables and found that the thermal and electrical properties of each layer in the cable insulation were improved to varying degrees under the short-term, high-temperature heat treatment, which was due to the annealing effect. Tzimas A et al [13] stressed the same XLPE-insulated AC cables under different electrothermal conditions and for various durations.…”
Section: Introductionmentioning
confidence: 99%